2015
DOI: 10.1016/j.clnu.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of dietary supplement use among college students

Abstract: College students appear more likely to use DS than the general population and many use multiple types of supplements weekly. Habits established at a young age persist throughout life. Therefore, longitudinal research should be conducted to determine whether patterns of DS use established early in adulthood are maintained throughout life. Adequate scientific justification for widespread use of DS in healthy, young populations is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
103
5
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 51 publications
23
103
5
3
Order By: Relevance
“…It could be that students using tobacco products may use NHP as a way to decrease the negative effects associated with tobacco. This could support a survey performed in five U.S. universities that reported that students using tobacco products are more likely to take several dietary supplements weekly [19]. It is suggested in this last study that students may incorrectly perceive the frequent use of dietary supplements to be a substitute for other healthy behaviors [19].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…It could be that students using tobacco products may use NHP as a way to decrease the negative effects associated with tobacco. This could support a survey performed in five U.S. universities that reported that students using tobacco products are more likely to take several dietary supplements weekly [19]. It is suggested in this last study that students may incorrectly perceive the frequent use of dietary supplements to be a substitute for other healthy behaviors [19].…”
Section: Discussionsupporting
confidence: 67%
“…This could support a survey performed in five U.S. universities that reported that students using tobacco products are more likely to take several dietary supplements weekly [19]. It is suggested in this last study that students may incorrectly perceive the frequent use of dietary supplements to be a substitute for other healthy behaviors [19]. This, however, warrants more investigation because in Native/Aboriginal culture, tobacco is traditionally used in ceremonies (e.g., prayers and offerings) and is also used as a medicine or as an anesthetic [32,33].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…It is also of interest to note that DS use appears to be increasing among young active civilians. Prevalence rates of 46% were observed from a survey conducted in 2007 (Goston and Correia 2010), and use prevalence of 65% has been reported from surveys conducted more recently on college campuses (Hoyte et al 2013;Lieberman et al 2015) or local gymnasiums (Lacerda et al 2015). Thus, the significant difference in DS use among the youngest soldiers in the present study between the 2 cohorts could reflect the increased DS use, in general, among young active individuals.…”
Section: Discussionmentioning
confidence: 56%